Business opportunities in Vietnam - Meng, Tan Teck; Meng, Low Aik (Singapore Prentice Hall, 1997)
Contents: Introduction; macro policy and reform; infrastructure for development; technology transfer; services sectors; business attitudes and behavioural issues; Singapore's investment initiatives; conclusion.
At head of title: Nanyang business report series
Includes bibliographical references
Keywords: Quản trị kinh doanh